2011
DOI: 10.1016/j.jvoice.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Wave Measurement and Visualization Techniques

Abstract: Organized vibration of the vocal folds is critical to high quality voice production. When the vocal folds oscillate, the superficial tissue of the vocal fold is displaced in a wave-like fashion, creating the so called “mucosal wave”. Because the mucosal wave is dependent on vocal fold structure, physical alterations of that structure cause mucosal wave abnormalities. Visualization and quantification of mucosal wave properties have become useful parameters in diagnosing and managing vocal fold pathology. Mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 43 publications
0
85
0
5
Order By: Relevance
“…In the early 20th century, direct laryngoscopy and endolaryngeal surgery migrated to the operating room for the promise of improved surgical precision (89). In laryngological and phoniatric diagnostics, white light laryngoscopy (WL) is the key procedure for functional investigation and early detection of neoplastic tissue (90). In fact, at present, white light laryngoscopy combined with biopsy is the standard diagnostic procedure in the assessment of laryngeal cancer and precancerous lesions.…”
Section: Endoscopymentioning
confidence: 99%
“…In the early 20th century, direct laryngoscopy and endolaryngeal surgery migrated to the operating room for the promise of improved surgical precision (89). In laryngological and phoniatric diagnostics, white light laryngoscopy (WL) is the key procedure for functional investigation and early detection of neoplastic tissue (90). In fact, at present, white light laryngoscopy combined with biopsy is the standard diagnostic procedure in the assessment of laryngeal cancer and precancerous lesions.…”
Section: Endoscopymentioning
confidence: 99%
“…Many studies have sought to compare and discuss the advantages, disadvantages, and the applicability of instruments such as ultrasound to electroglottography, video fluoroscopy, and computerized tomography (33)(34)(35)(36) . Many of these techniques are widely used in the medical field and by speech language pathologists, but the ultrasound, for example, is a method that requires study and has been recruited on a larger scale for research in the field of Speech Language Pathology and Audiology.…”
Section: Ultrasound and Voicementioning
confidence: 99%
“…The five studies reported the importance of using the method of ultrasound combined with other techniques, what could decrease the risk of postoperative complications (36) , determine laryngeal segments with better accuracy (35) , determine variations in muscle length (34) , as well as contribute to diagnosis and to an effective treatment plan (33,37) .…”
Section: Ultrasound and Voicementioning
confidence: 99%
“…En estas imágenes es posible analizar con precisión los detalles del comportamiento vibratorio (15,16), pero su verdadera importancia radica en que permiten la evaluación detallada de fenómenos que de otra manera serían imposibles de analizar. Ejemplos de ello son: la medición del tiempo en que se inicia la vibración ( Fig.…”
Section: A Laringoscopia De Alta Velocidad Y Videoquimografíaunclassified